2008
DOI: 10.1523/jneurosci.2929-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Scales of Neuronal Correlation in Primary Visual Cortex

Abstract: The spiking activity of cortical neurons is correlated. For instance, trial-to-trial fluctuations in response strength are shared between neurons, and spikes often occur synchronously. Understanding the properties and mechanisms that generate these forms of correlation is critical for determining their role in cortical processing. We therefore investigated the spatial extent and functional specificity of correlated spontaneous and evoked activity. Because feedforward, recurrent, and feedback pathways have dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

131
707
10
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 567 publications
(876 citation statements)
references
References 87 publications
131
707
10
1
Order By: Relevance
“…We next studied the dynamics of the population in response to short acoustic clicks (duration, 5 ms; interclick interval, 2.5 or 3.5 s). We used a sliding spike count window (T = 50 ms) and computed the averaged instantaneous rate, spike count correlation ρ(t) (2,14,15), and spike count Fano factor (11)(12)(13) by performing the statistics across repeated stimulus presentations and averaged over single units or single-unit pairs (Methods). Similarly, we computed the instantaneous silence density S(t) using 20-ms bins.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We next studied the dynamics of the population in response to short acoustic clicks (duration, 5 ms; interclick interval, 2.5 or 3.5 s). We used a sliding spike count window (T = 50 ms) and computed the averaged instantaneous rate, spike count correlation ρ(t) (2,14,15), and spike count Fano factor (11)(12)(13) by performing the statistics across repeated stimulus presentations and averaged over single units or single-unit pairs (Methods). Similarly, we computed the instantaneous silence density S(t) using 20-ms bins.…”
Section: Resultsmentioning
confidence: 99%
“…To describe the fluctuations of r(t), we used a rate model with adaptation a(t) where the dynamics were given by the following (22,25,28): τ r dr dt = −rðtÞ + ϕðαrðtÞ − aðtÞ + IðtÞ − θÞ, τ a da dt = −aðtÞ + βrðtÞ, [2] where θ = 2 was the activation threshold and the external input I(t) = I + stim(t) + σξ(t) was composed of constant term I (range, 0-4 a.u. ), the stimulus step function (amplitude, 60 a.u.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the network interaction between these types of morphofunctional discriminated units has still largely not been investigated. Neuronal correlations have been shown to decay with space in primary visual cortex, possibly caused by the highly structured nature of inputs (18). In parallel, it has been shown that, in the rodent hippocampus, at the top of cortical processing, such an effect of distance on neuronal correlations was also present and was different for excitatory and inhibitory cells (19).…”
mentioning
confidence: 99%